Seismic responses of reinforced concrete intermediate short columns failed in different modes. (1st March 2020) - Gu, XiangLin; Hua, JingJing; Cai, Mao
Highlights: Five RC intermediate short columns failed in different modes were tested. Their crack patterns, strength, stiffness, and hysteretic behavior were investigated. Shear-flexure interaction was studied by comparing their component deformations. A model including two sub-elements describing flexure and shear response was provided. Comparison of the model and test results indicates its accuracy and simplicity. Abstract: The main objective of this paper is to observe the seismic responses of intermediate short columns failed in different modes and develop an efficient analytical model reproducing their behavior based on the experimental observation, which will eventually be used to execute assessments of seismic behavior for existing RC frame structures. Five RC columns designed to fail in different modes were tested under constant axial load plus unidirectional cyclic lateral loading, the effect of height-to-depth ratio, axial load ratio and transverse reinforcement ratio on their seismic response was investigated. Interaction of flexural and shear responses was studied by comparing their component deformations. Test results shown that for a column whose shear-resisting mechanism was significantly degraded, flexural responses would not develop while shear responses increased rapidly. However, for a column possessing a shear-resisting mechanism without significant deterioration, shear responses would stably increase as flexural responses continued to develop over the entire range of imposed displacement ductility. In the proposed model, flexural behavior was estimated by the multi-springs model employing the hysteretic behavior of steel and concrete materials. Pre-peak monotonic shear behavior was modeled by applying the truss model, and the degrading slope after shear failure was estimated by the shear-friction model. The shear hysteretic model proposed by Ozcebe and Saatcioglu was expanded for seismic response evaluation before and after failure. The column model was validated with results of test columns both from this paper and the literature.